Food safety knowledge and attitudes among fish vendors in informal markets in Ilorin, Nigeria: a cross-sectional study - Ibraheem Ghali-Mohammed; Tajudeen Opeyemi Isola; Ismail Adewuyi Adeyemo; Rafiu Adebisi Kadir; Hawau Motunrayo Ambali; Nma Bida Alhaji; Ismail Ayoade Odetokun (Discover Food, 2024)
Abstract Background With the rising demand for fish and increasing concerns about foodborne illnesses, understanding vendors' perspectives is critical for enhancing food safety standards. This cross-sectional study assessed food safety knowledge and attitudes among fish sellers operating in informal fish markets in Ilorin Metropolis, Nigeria, using a structured questionnaire administered via face-to-face interviews between October and December 2023. Methods A total of 240 fish vendors completed the survey. A stepwise backward binary logistic regression model was used to identify the independent factors associated with good knowledge or satisfactory attitudes toward food safety among fish vendors. Results Over 62.5% of the respondents had good food safety knowledge, particularly in areas such as personal hygiene and cross-contamination. However, misconceptions about foodborne diseases persist. While attitudes toward food safety were generally positive, certain practices such as wearing protective gear were less endorsed. Demographic factors significantly influenced both knowledge and attitudes. Logistic regression analysis revealed that respondents in older age groups were at least 11 times more likely to have satisfactory attitudes (OR: 10.5, 95% CI: 1.8–62.8, p = 0.015) toward food safety. Additionally, participants with smaller family sizes were four times more likely to display satisfactory attitudes toward fish safety. Conclusion These findings underscore the need for targeted interventions, including training programs and government regulations, to improve fish vendors’ food safety practices. Strengthening education and enforcement measures is crucial for safeguarding public health and enhancing the quality of fish products in informal markets in Ilorin.